Genetic Diversity of Calliandra (Calliandra calothyrsus Meissn.) Seedling from West Java - Danu Danu; Aam Aminah; Naning Yuniarti; Dida Syamsuwida; Deddy Dwi Nur Cahyono; Nurmawati Siregar; YMM Anita Nugraheni; Kresno Agus Hendarto (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2020)
Kaliandra (Calliandra calothyrsus Meissn.) is a potential species as a feedstock for making wood pellets with a heating value of 4,722 cal/g. The objective of this study was to determine the genetic diversity of kaliandra seedlings in the nursery from four populations in West Java, namely Cianjur, Garut, Sukabumi, and Sumedang. Seed collection is carried out from each population, then germinated at the nursery of the Nagrak Research Station, Bogor Regency. Using a Completely Randomized Block Design, with 4 replications from each population, each repetition consisted of 10 seedlings, the results showed that the best height growth (59.75 cm) was produced from Cianjur and the best diameter (4.44 mm) was produced from Sukabumi. Seedling height can be used as a criterion for the selection of parent trees at the nursery level because the high seedling heritability (0.333 and 0.656) is relatively higher than the diameter of the seedlings (0.114 and 0.445), both individuals and families. The genetic correlation between traits shows a high value that is equal to (0.562).